Regulatory Framework for Blue Sukuk: Enhancing Blue Economy by Reinforcing Shariah Investment - Mentari, Nikmah; Romadoni, Rahayu Mulia (Fakultas Hukum Universitas Hang Tuah, 2025)
The emergence of Blue Sukuk presents a strategic opportunity to mobilize capital for sustainable development in Indonesia's blue economy. This research delves into the regulatory framework necessary to support the implementation of Blue Sukuk, a financial instrument rooted in Islamic finance principles and designed to fund projects promoting oceanic sustainability. Indonesia's rich marine biodiversity and extensive coastline underscore the potential of Blue Sukuk to attract diverse investors and strengthen capital markets. Effective regulatory measures are pivotal in ensuring compliance, transparency, and investor confidence. The method of this research is normative-juridical methods. This research is statute and conceptual approach. This paper examines Indonesia-specific regulatory considerations and proposes strategies to optimize the role of Blue Sukuk in fostering economic resilience and environmental stewardship in the archipelago nation. Meanwhile, the Sukuk is based on sustainability development on Indonesian Financial Services Authority (OJK) Regulation’s Number 18 Year 2023. It is a big opportunity for Shariah investment in Indonesia where Islam is the biggest Islamic religion in this country.